ArcGIS 9.3 ed i database spaziali: gli scenari di utilizzo - Bartoli, Francesco (GEOmedia, 2009)
ArcGis 9.3 and spatial databases: application sceneries The latest news from ESRI suggests that it will soon be possible to link to the PostgreSQL database. This resulted in a collaboration between the PostGis geometry model with SDOGEOMETRY - the oracle database - a hierarchial and spatial design database. This had a direct impact on the PMI review and the business models of local governments. ArcSde would be replaced by Zig-Gis 2.0 providing greater offerings to the GIS community. Harnessing this system will take advantage of human resources to aid in the design of potent conceptual data models. Further funds are still required to promote the product under a prominent license.